Sex similarities and differences in the reverse and anti-remodeling effect of pressure unloading therapy in a rat model of aortic banding and debanding - Ruppert, Mihály; Barta, Bálint András; Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Oláh, Attila; Sayour, Alex Ali; Benke, Kálmán; Nagy, Dávid; Bálint, Tímea; Karck, Matthias; Schilling, Oliver; Merkely, Béla; et al. (American journal of physiology. Heart and circulatory physiology, 2022)
Investigating the effect of sex on pressure unloading therapy in a clinical scenario is limited by several nonstandardized factors. Hence, we sought to study sex-related similarities and differences under laboratory conditions. Pressure overload was induced in male and female rats by aortic banding (AB) for 6 and 12 wk. Age-matched sham-operated animals served as controls. Pressure unloading was performed by aortic debanding at week 6. Different aspects of myocardial remodeling were characterized by echocardiography, pressure-volume analysis, histology, qRT-PCR, and explorative proteomics. Hypertrophy, increased fetal gene expression, interstitial fibrosis, and prolonged active relaxation were noted in the AB groups at week 6 in both sexes. However, decompensation of systolic function and further deterioration of diastolic function only occurred in male AB rats at week 12. AB induced similar proteomic alterations in both sexes at week 6, whereas characteristic differences were found at week 12. After debanding, regression of hypertrophy and recovery of diastolic function took place to a similar extent in both sexes. Nevertheless, fibrosis, transcription of β-myosin-to-α-myosin heavy chain ratio, and myocardial proteomic alterations were reduced to a greater degree in females than in males. Debanding exposed anti-remodeling properties in both sexes and prevented the functional decline in males. Female sex is associated with greater reversibility of fibrosis, fetal gene expression, and proteomic alterations. Nevertheless, pressure unloading exposes a more pronounced anti-remodeling effect on the functional level in males, which is attributed to the more progressive functional deterioration in AB animals. - - NEW & NOTEWORTHY The present study is the first to assess the role of sex on pressure unloading-induced reverse and anti-remodeling in a rat model of aortic banding and debanding. Our data indicate that female sex is associated with a greater reversibility of fibrosis, fetal gene expression, and proteomic alterations compared with males. Nevertheless, pressure unloading exposes more anti-remodeling effect on the functional level in males, which is attributed to the more rapid functional deterioration in aortic-banded animals.